Atrial Arrhythmia in Atrial Septal Defect Patient: A Case Report and Review of Literature - Indah Paranita; Lucia Kris Dinarti; Bambang Irawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Atrial fibrillation (AF) and atrial flutter are the most common cardiac arrhythmias associated with atrial septal defects (ASD) in adult patients. The incidence could be as high as 52% in patients ages 60 years or more.Patient with congenital heart disease who developed atrial arrhythmias had a >50% increased stroke risk. Nevertheless, studies regarding the pathophysiological mechanism underlying the high incidence of atrial fibrillation in adult patients with ASD remain relatively few. We reported a female 46 years referred to Sardjito hospital with chest discomfort and palpitation. ECG showed atrial flutter, 90 beat per minute, incomplete RBBB, RAD and RVH. Transthoracal echocardiography shown ASD left to right shunt with diameter 1.2 -1.8 cm, LA, RA and RV dilatation, with normal systolic function. From right heart catetherization, the result is ASD High Flow Low Resistance, with pulmonary hypertension (mPAP 44 mmHg).The consequences of left to right shunt across an ASD is RV volume overload and pulmonary overcirculation. Atrial arrhytmia are a common result of long standing right side heart volume and pressure overload. The idea of combining ASD closure and arrhythmia intervention is another approach to consider.